Design and Technology Teacher in TVET: A View on Thinking Style and Inventive Problem-Solving Skill - Tze Kiong, Tee; Saien, Shanty; Rizal, Fahmi; Sukardi,; Risfendra,; Yee, Mei Heong; Mohamad, Mimi Mohaffyza; Othman, Widad; Azman, Mohamed Nor Azhari; Azid, Nurulwahida (Journal of Technical Education and Training, 2019)
Teachers play an important role to help student in solving problem in school and consequently preparing for their future career. Teachers can be the most important feature to expose thinking style in class. This is the implication of Technical and Vocational Education and Training programme which requires the students to be able to think creatively and critically in problem-solving. As inventive problem solving is known to be creative assessment methods for innovation, it is needed to guide Design and Technology teachers to expose the student new technique of solving a problem. This study attempts to investigate teachers’ perception of their thinking style and inventive problem-solving skill. The importance of thinking styles in inventive problem-solving skill and the factors contributing to the achievement to inventive problem solving are also discussed. Data were collected from 367 Design and Technology teachers across Malaysia. Data obtained were analyzed descriptively. This study confirmed that teachers know the role of thinking style in solving a problem. They also admit that inventive problem-solving skill is important but half of them still having problem to master the skills. Problem identification is claimed to be a vital process in solving a problem but yet, majority of them still facing problem in finding the root cause. As a counter-measures on this miss-alignment, modules are needed by teachers to help them integrating their thinking styles into teaching and learning in class. Module also acts as teaching aids for teachers in guiding them solving inventive problems.